Risk factors and consequences of decreased kidney function in nursing home residents: A longitudinal study. Issue 5 (6th May 2016) - Bolmsjö, Beata Borgström; Mölstad, Sigvard; Gallagher, Martin; Chalmers, John; Östgren, Carl Johan; Midlöv, Patrik
Abstract : Aim: The aim of the present study was to study the renal function and the relationship of deterioration in renal function with major outcomes in elderly nursing home residents. A second aim was to compare the internationally recommended formulae for estimated glomerular filtration rate (eGFR) consisting of both creatinine and cystatin C in a nursing home population. Methods: A total of 429 patients from 11 nursing homes were included during 2008–2011. GFR was estimated, from formulae based on both creatinine and cystatin C, at baseline and after 1 and 2 years. The patients were divided into groups based on chronic kidney disease level, and comparisons were made for mortality, morbidity, the use of medications and between the different formulae for eGFR. Results: Survival was lower in the groups with lower renal function. Over 60% of the residents had impaired renal function. Those with impaired renal function were older, had a higher number of medications and a higher prevalence of heart failure. Higher number of medications was associated with a greater risk of rapid decline in renal function with an odds ratio of 1.2 (95% confidence interval 1.06–1.36, P = 0.003). The compared eGFR formulae based on both cystatin C and creatinine were in excellent concordance with each other. Conclusions: Decreased renal function was associated with increased mortality. A majority of nursing home residents had declining renal function, which should be considered when prescribing medications. The more medications, the higher the risk for rapidly declining renal function.Geriatr Gerontol Int 2017; 17: 791–797.